2016
DOI: 10.1177/0001699316654529
|View full text |Cite
|
Sign up to set email alerts
|

Preschool education as the great equalizer? A cross-country study into the sources of inequality in reading competence

Abstract: In this study we examine the extent to which preschool education can reduce social background differentials in learning outcomes across countries; our focus is on whether the benefits of preschool attendance for children depend on other family inputs such as parents' education and their pedagogical involvement during early childhood. We use the 2011 Progress in International Reading Literacy Study, which provides a standardized measure of reading literacy among students in 4th grade. Our sample contains data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
4
23
0
Order By: Relevance
“…As much as researchers and their educator partners might strive to use data to understand and address inequities, they cannot do so alone. Schools cannot continue to be asked to play the role of the “great equalizer” (Cebolla-Boado, Radl, & Salazar, 2017; Downey, von Hippel, & Broh, 2004; von Hippel, Workman, & Downey, 2018), while inequalities and inequities go largely unchecked outside their doors. Unless we do more, as a society, to address rampant disparities, schools will always and forever be faced with having to ameliorate the symptoms of inequality, not its causes.…”
Section: Big Problems Big Solutionsmentioning
confidence: 99%
“…As much as researchers and their educator partners might strive to use data to understand and address inequities, they cannot do so alone. Schools cannot continue to be asked to play the role of the “great equalizer” (Cebolla-Boado, Radl, & Salazar, 2017; Downey, von Hippel, & Broh, 2004; von Hippel, Workman, & Downey, 2018), while inequalities and inequities go largely unchecked outside their doors. Unless we do more, as a society, to address rampant disparities, schools will always and forever be faced with having to ameliorate the symptoms of inequality, not its causes.…”
Section: Big Problems Big Solutionsmentioning
confidence: 99%
“…However, it is necessary to bear in mind that for the calculation of this indicator the schooling rates of different age cohorts (from six to 24 years) would have to be taken into account, and it is not possible to determine whether there is a differential effect at a given age. In this regard, numerous studies have shown the impact of preschool education on educational outcomes (Cebolla‐Boado et al., 2017).…”
Section: Empirical Analysismentioning
confidence: 99%
“…A growing body of evidence points to parental education attainment as the most powerful predictor of children's cognitive and academic outcomes (Magnuson et al, 2009;Harding et al, 2015;Davis-Kean et al, 2021;Waters et al, 2021). More educated parents tend to have access to a greater number of resources and provide their children with more stimulating activities, toys, books, and educational opportunities both in and outside the home (Cebolla-Boado et al, 2017;Davis-Kean et al, 2021). As evidence suggests that mothers' education may be more influential than father's education for early learning and development (Cebolla-Boado et al, 2017;Conway et al, 2018), we defined SES in terms of maternal education in the current study.…”
Section: Self-regulation Skills As Mediators Between Ses and Math Achievementmentioning
confidence: 99%